2022
DOI: 10.3390/ijms23147669
|View full text |Cite
|
Sign up to set email alerts
|

Increased Acetylcholine Levels and Other Brain Effects in 5XFAD Mice after Treatment with 8,14-Dihydroxy Metabolite of Efavirenz

Abstract: Efavirenz (EFV), an FDA-approved anti-HIV drug, has off-target binding to CYP46A1, the CNS enzyme which converts cholesterol to 24-hydroxycholesterol. At small doses, EFV allosterically activates CYP46A1 in mice and humans and mitigates some of the Alzheimer’s disease manifestations in 5XFAD mice, an animal model. Notably, in vitro, all phase 1 EFV hydroxymetabolites activate CYP46A1 as well and bind either to the allosteric site for EFV, neurotransmitters or both. Herein, we treated 5XFAD mice with 8,14-dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Mechanistically, CYP46A1 activation by EFV increased the rates of the mevalonate pathway as well as sterol flux through the plasma membranes and thereby altered physico-chemical properties of plasma membranes and membrane-dependent events, such as synaptic transmission and phosphorylation of cytoskeletal and other proteins [ 26 , 27 ]. In addition, increased sterol flux was shown to increase in 5XFAD mice total brain acetyl-CoA content, energetic state of brain mitochondria, and brain acetylcholine levels [ 27 , 28 ]. A model of how one enzyme can control multiple and apparently unrelated processes in the brain was proposed [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, CYP46A1 activation by EFV increased the rates of the mevalonate pathway as well as sterol flux through the plasma membranes and thereby altered physico-chemical properties of plasma membranes and membrane-dependent events, such as synaptic transmission and phosphorylation of cytoskeletal and other proteins [ 26 , 27 ]. In addition, increased sterol flux was shown to increase in 5XFAD mice total brain acetyl-CoA content, energetic state of brain mitochondria, and brain acetylcholine levels [ 27 , 28 ]. A model of how one enzyme can control multiple and apparently unrelated processes in the brain was proposed [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…We called these two sites EFV-and L-Glu-binding, respectively, and showed that when activators bind to each site simultaneously, their effect on CYP46A1 activity is synergistic [33,35]. We established that EFV monohydroxy metabolites can bind to both CYP46A1 allosteric sites, whereas 7,8-dihydroxy EFV [7,8diOH EFV, either (S) or (rac)] only interacts with EFV-binding sites, and 8,14-dihydroxy EFV [8,14diOH EFV, either (S) or (rac)] binds only to the L-Glu-binding site [31].…”
Section: Introductionmentioning
confidence: 95%
“…Herein, (rac)-7,8diOH EFV (called 7,8diOH EFV hereafter) was investigated to compare its brain effects with those of 8,14diOH EFV. We established that at a dose (0.1 mg/kg of body weight per day), delivery route (in drinking water), and treatment duration (6 months, from 3 to 9 months of age) which were similar to treatments with 8,14diOH EFV and (S)-EFV [16,31], 7,8diOH EFV also activated CYP46A1 in the brain of 5XFAD mice. However, the extent of the enzyme activation and other therapeutically relevant effects were not as pronounced as with (S)-EFV and 8,14diOH EFV.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations